SCOR Model for a Dual-Channel Supply Chain using Drop Shipping to Reduce Overstock in Small- and Medium-Sized Retail Enterprises - Francia-Arias, G. (2020)
Sales are central to retail companies. One of the main problems for these companies is when products are sold later than expected, causing overstock due to lower inventory turnover, which increases inventory levels. Therefore, for many retailers, it is important to solve this problem. This is mostly applicable to companies engaged in sales; however, if we take into account the main supplier and the way they act within the supply chain, we must also consider an additional approach. Since online sales are a major innovation brought about by the new digital era, it is standard for sales strategies to focus on this new requirement of customers. In this way, the main supplier takes a leap forward on Internet sales, creating another sales channel. This is when companies under the supply chain start losing sales. According to the above, a dual supply chain model was suggested using the SCOR model and drop shipping. After the improvement proposal was implemented, the company reported a reduction of approximately S/13,000 when comparing the first quarter of 2018 to that of 2019.